2019
DOI: 10.1590/1414-431x20198385
|View full text |Cite|
|
Sign up to set email alerts
|

Schizandrin A exerts anti-tumor effects on A375 cells by down-regulating H19

Abstract: Malignant melanoma (MM) is one of the malignant tumors with highly metastatic and aggressive biological actions. Schizandrin A (SchA) is a bioactive lignin compound with strong anti-oxidant and anti-aging properties, which is stable at room temperature and is often stored in a cool dry place. Hence, we investigated the effects of SchA on MM cell line A375 and its underlying mechanism. A375 cells were used to construct an in vitro MM cell model. Cell viability, proliferation, apoptosis, and migration were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Moreover, the migration and invasion of AGS cells were both decreased after SchA treatment, and SchA at the concentration of 30 µM exerted the most obvious inhibitory effects on the migration and invasion of AGS cells. Furthermore, the apoptosis of AGS cells was significantly induced by SchA, which was in line with previous findings suggesting the promoting role of SchA in the apoptosis of human cancer cells (7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the migration and invasion of AGS cells were both decreased after SchA treatment, and SchA at the concentration of 30 µM exerted the most obvious inhibitory effects on the migration and invasion of AGS cells. Furthermore, the apoptosis of AGS cells was significantly induced by SchA, which was in line with previous findings suggesting the promoting role of SchA in the apoptosis of human cancer cells (7).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, it can promote the cell cycle arrest, apoptosis and cell death induced by heat shock transcription factor 1, thereby impeding the proliferation of colorectal cancer cells (6). SchA can obstruct the proliferation and invasion of melanoma cells and the phosphorylation of PI3K/AKT by repressing H19 imprinted maternally expressed transcript expression (7). In addition, it can modulate the overactivation of Wnt and activate endoplasmic reticulum (ER) stress to induce the cell cycle arrest and apoptosis of triple-negative breast cancer cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…H19 has been reported to regulate autophagy in various types of cancer, and its aberrant expression was associated with tumorigenesis. 38,39 The role of H19 in periodontitis has not been investigated previously. In the present study, we determined the expression of H19 in PDLCs under TNFα and LPS stimulation as well as in inflamed periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, studies investigating the potential antitumor effects of SchA have been gradually increasing. It was previously reported that SchA can inhibit cell proliferation, induce cell apoptosis, inhibit cell invasion and tumor metastasis in breast cancer, ovarian cancer, choriocarcinoma, thyroid cancer and colorectal cancer (31,(35)(36)(37)(38)(39)(40)(41)(42), in addition to enhancing drug efficacy in NSCLC and colon carcinoma (43,44) or overcome drug resistance in breast cancer and esophageal carcinoma (30,45,46). In particular, Xian et al revealed that SchA combined with gefitinib could inhibit proliferation whilst promoting apoptosis in gefitinib-resistant NSCLC cells (43).…”
Section: Schizandrin a Can Inhibit Non-small Cell Lung Cancer Cell Proliferation By Inducing Cell Cycle Arrest Apoptosis And Autophagymentioning
confidence: 99%